The Concept Of Optimal Workplace In Providing A Great Experience To Improve Work Professionalism In The Interior Design Of Pln Corporate University, Ragunan, Jakarta - et al., Asep Yudi Permana (International Journal of Advanced Science and Technology, 2020)
PLN Corporate University is one of the facilities established by PLN Inc. to develop the potentials ofsubsidiaries and educate employees to gain competence and professionalism. One of its roles is tobalance the company’s needs with learning activities using an integrated information system. PLNCorporate University acts as a medium in enhancing excellence in the areas of leadership, competence,and high work ethics. To make it happen, it needs to be supported by spatial planning which supportsthe work performance and productivity of all employees. Thus, PLN Corporate University needs anoffice concept which emphasizes on promoting sustainability and on understanding work activitieswhich are more flexible, dynamic, and interconnected, among office spaces, technology, and functions.An office with good characteristics is not only feasible but also able to stimulate the employees toachieve accomplishments in accordance with the employees’ potentials. The development of buildingand information technology has a major influence on human activities in a space, where offices notonly fulfill the need to work, but also have other advantages, such as providing the improvedenvironmental quality and work quality, stimulating the interaction and teamwork among staffs anddepartments, and encouraging the emergence of innovation through creative processes that occur atthe work environment. To achieve the desired condition, the basic concepts applied in the interiordesign of PLN Corporate University are open-space, flexible, simple, inspiring, performing,phenomenal, and creative in order to realize its vision and mission as the center of excellence inlearning.